O estímulo à leitura em bibliotecas prisionais por meio do desenvolvimento de dinâmicas culturais - Fernandes, Raquel Gonçalves da Silva de Araújo (2019)
This work presents a study that has as general objective the development of a model of cultural mediation to encourage the reading of informational items that are not consumed by inmates of the Female Prison of Sergipe – PREFEM-SE. For this, the methodology used was a phenomenological study with qualitative approach, and the universe of research represented by the inmates of PREFEM-SE. Data collection was based on questionnaires and interviews, in addition to observations and data analyzes that allowed a diagnosis that served as the basis for the design of the intervention action. In this action, activities were conducted with three groups of readers and non-readers, 10 women per group, where topics selected from the diagnosis were: Domestic violence, Feminism and Maternity in prison, subjects that were present in selected short films and texts. After the conclusion of these activities, the inmates were invited to express themselves through discussions and elaborating posters, expressing their interpretation of the activity and presenting them to each other. The results pointed out a connection between the library and the inmates, related to the physical and dimensional space of the site, as well as their contact with similar realities and the representativeness shown in the texts and short films. It is concluded that the activity generated positive elements on the discussions of texts and short films, notions of interpretation, correlation among elements and the creative approach through the posters, besides bringing readers to the universe of books and reading and giving dynamicity to the library space.